Modulation of the photophysical properties of multi-BODIPY-siloxane conjugates by varying the number of fluorophores. (July 2022) - Pakhomov, Alexey A.; Kim, Eleonora E.; Kononevich, Yuriy N.; Ionov, Dmitriy S.; Maksimova, Margarita A.; Khalchenia, Veronika B.; Maksimov, Eugene G.; Anisimov, Anton A.; Shchegolikhina, Olga I.; Martynov, Vladimir I.; Muzafarov, Aziz M.
Abstract: A series of multifluorophore compounds with two, four, six and eight BODIPY residues linked to a siloxane core via a flexible spacer was synthesized. An increasing number of BODIPY units caused an enhanced propensity to chromophore aggregation with characteristic photophysical effects evoked by the aggregation. The increase in the number of fluorophores additionally resulted in considerable increase in molar extinction coefficient. Meanwhile, a slight drop of the extinction coefficient as calculated per a single chromophore was detected. Multifluorophore conjugates showed a significant broadening of fluorescence emission bands in polar solvents and a substantial decrease in the fluorescence quantum yield due to the aggregation-caused quenching. Time resolved fluorescence measurements of multifluorophore compounds in different solvents showed that the fluorescence decays have a multiexponential character and strongly depend on the number of fluorophores in the conjugate, polarity/viscosity of the solvent and the detection wavelength. Graphical abstract: Image 1 Highlights: A series of BODIPY-siloxane conjugates with 2, 4, 6, and 8 fluorophores in a single molecule was synthesized. The dyes showed a pronounced solvatochromic behavior. A moderate quenching of fluorescence. Decrease of specific extinction coefficient calculated per a single chromophore. Fluorescence lifetimes depend on the detection wavelength and solvent.